SECONDARY SCHOOLS, AND VOCATIONAL SCHOOLS IN THE ATMOSPHERE AND HIS POLLUTION” IS THE SUBJECT OF INDEPENDENT TEACHING THE ROLE OF EDUCATION - Hotamov, Jaxongir (Физико-технологического образование, 2022)
This article in all the countries of the world, as happens in other regions in central asia, Uzbekistan and pressing environmental problems, environmental problems in uzbekistan had also become the most dangerous clean air, drinking water, soil structure and the disorder of the nation to the aral sea problem solving should be come of the most basic function of. In addressing this problem, rebuild the island and together they cited the issues of the preservation of the environment